The Effect of Banana Peel Biosorbent (Musa Acuminate) on Water Clarity, pH, TDS, and DO Levels in Household Wastewater in Bandung - Fatharani, Aulia; Al-Wafi, Ok M Abthal; Marhamah, Yualinda Durotul; Shani, Nadiya Syafia; Fitriani, Any; Yulianty, Nurfitri (Universitas Pendidikan Indonesia and Konsorsium Biologi Indonesia, 2025)
Banana peel consists of nitrogen atoms, sulfur and organic materials such as carboxylic acids that can function to bind pollutant molecules. The purpose of this research is to make King Banana (Musa acuminate) peel as filtration media to improve the physical quality of water including water clarity, pH value, TDS and Dissolved Oxygen (DO). There are three stages carried out, including preparation of banana peel waste, adjusting the media and filtration time and data analysis. The preparation process of banana peel waste is done by cleaning the banana peel then dried and mashed, then alkalized using 0.5 N NaOH. Then a variation in the amount of filtration media is made, namely: 60 g, 80 g and 100 g of plantain peels formulated using an additional 30 grams of zeolite with variations in filtration time, namely: 3 hours, 6 hours and 9 hours. The filtration results obtained using a variation of 100 grams of filtration media with a filtration time of 9 hours is the best media combination where the results obtained show an increase in water clarity, pH 5.41 and an increase in DO (Dissolve oxygen) of 20.